A Surface Coordination Network Based on Copper Adatom Trimers1. Issue 47 (22nd September 2014) - Bebensee, Fabian; Svane, Katrine; Bombis, Christian; Masini, Federico; Klyatskaya, Svetlana; Besenbacher, Flemming; Ruben, Mario; Hammer, Bjørk; Linderoth, Trolle R.
Abstract Surface coordination networks formed by co‐adsorption of metal atoms and organic ligands have interesting properties, for example regarding catalysis and data storage. Surface coordination networks studied to date have typically been based on single metal atom centers. The formation of a novel surface coordination network is now demonstrated that is based on network nodes in the form of clusters consisting of three Cu adatoms. The network forms by deposition of tetrahydroxybenzene (THB) on Cu(111) under UHV conditions. As shown from a combination of scanning tunneling microscopy, X‐ray photoelectron spectroscopy, and density functional theory calculations, all four hydroxy groups of THB dehydrogenate upon thermal activation at 440 K. This highly reactive ligand binds to Cu adatom trimers, which are resolved by high‐resolution STM. The network creates an ordered array of mono‐dispersed metal clusters constituting a two‐dimensional analogue of metal–organic frameworks.